A novel 3D heteropoly blue type photo-Fenton-like catalyst and its ability to remove dye pollution. (April 2018) - Fei, Bao-Li; Zhong, Jian-Kai; Deng, Ni-Ping; Wang, Jiang-Hong; Liu, Qing-Bo; Li, Yang-Guang; Mei, Xiang
Abstract: A environment-friendly 3D inorganic heteropoly blue (HPB) Ba2 Na2 [HPW V 4 W VI 8 O40 ]·26H2 O was directly synthesized by hydrothermal method and characterized by means of ICP, IR, XPS, X-ray single crystal and X-ray powder diffraction. It was an efficient heterogeneous photo-Fenton-like catalyst to degrade anionic dye methyl orange under visible light irradiation. It removed cationic dyes methylene blue in neutral environment and rhodamine B in acidic condition via flocculation. The removal efficiency of methylene blue and rhodamine B by flocculation was more than 95%. Moreover, it could degrade methyl orange and flocculate rhodamine B at the same time. For MO and MO-RhB solutions, the degradation rates of MO in 60 min were 85.5% and 49.1%, respectively. Furthermore, the possible pathways for the production of active species in the MO degradation reaction were discussed. This is the first HPB constructed with 4e-reduced phosphotungstate, Ba and Na ions, having the properties of photo-Fenton-like catalyst and flocculant. Highlights: 3D inorganic heteropoly blue (HPB) was an effective remover for anionic and cationic dyes. The HPB eliminated MB and RhB from water with efficiency above 95%. An efficient heterogeneous Fenton-like catalyst to degrade MO under visible light irradiation. Bleaching methyl orange and flocculating rhodamine B at the same time.